Laser‐Assisted Lithotripsy in the Minimally Invasive Treatment of Sialolithiasis. (23rd August 2013) - Phillips, James D.; Withrow, Kirk
Abstract : Objectives: In the minimally invasive treatment of sialolithiasis, lasers can be used to fracture stones, allowing for the endoscopic extirpation of larger lesions. The purpose of the current study was to evaluate outcomes following the use of the holmium YAG laser for intracorporeal salivary lithotripsy. Methods: Review of prospectively collected data regarding patients who underwent interventional sialoendoscopy for sialolithiasis was performed, recording patient demographics, surgical findings, and clinical outcomes. Patients who were treated with intracorporeal laser lithotripsy were compared with those who had simple basket retrieval or endoscopic assisted open removal. Patients were surveyed by phone for current symptom follow‐up. Results: Thirty‐one patients (average age 56, range 14‐84) were treated for sialolithiasis with endoscopic techniques at our academic institution from 2011‐2012. Sialoliths averaged 5.9 mm in size (range 2‐20mm), arising from the submandibular ducts (n=20), parotid (n=10), or both (n=1). The holmium YAG laser was used in 16 patients. Of these cases, 6 patients required additional maneuvers to open the duct to allow for stone extraction compared to 10 cases in which the laser was not used. At last follow‐up, 77% of patients who had laser assistance reported improvement of symptoms compared with 56% of the non‐laser group. Complications in all patients included ductal stenosis (n=1), residual stone fragments (n=2), salivary fistula (n=1), and the need for additional procedures (n=6). Conclusions: The results of our series indicate that intracorporeal laser assisted lithotripsy is an effective addition to the armamentarium of sialoendoscopy.